Determination of attitudes and behaviours in relation to active aging in individuals aged over 60 who are living in nursing homes [Bakım evlerinde yaşayan 60 yaş üstü bireylerin etkin yaşlanma konusunda tutum ve davranışlarının belirlenmesi] - (:unkn) unknown (Marmara University, 2014)
Aim: As the population ages, it is important to recognize the health problems of the elderly in relation to individual and public health issues. Our aim was to determine the daily habits and health-related behaviours of an aging population concerning factors such as nutritional status, physical and social activity levels and chronic health problems. Patients and Methods: This is a cross-sectional study. The study included 175 participants over 60 years of age that were mentally healthy and living in different nursing homes. A minimental test, a study questionnaire, a geriatric depression scale and an activities of daily living (ADL, physically dependent on others) scale were applied to the participants face to face. Results: Eighty-five (48.6%) of the participants were male. 42.3% of the participants did not do any regular physical exercise in their life time. The frequency of regular physical exercise was higher in the physically non-dependent to others (p=0.005) group in the ADL scale. Depression and ADL scores increased with increasing body mass index (BMI) (p= 0.012 and p= 0.010, respectively). In continuous medication users depression is quite high when compared to those who do not use medication constantly (p= 0.002). With increasing working years, there was a tendency to a decrease in scores of the physically dependent on others group in ADL. Conclusion: Regular physical exercise and an active work history both have a negative correlation on dependency in ADL in later years. Depression is more common among individuals who are on medication due to chronic health problems. A greater BMI was related to a higher frequency of depression and to dependency in ADL. © 2014, Marmara University. All rights reserved.
Keywords: Active aging; Depression; Elderly health; Exercise